Use of Baidu Index to Track Chinese Online Behavior and Interest in Kidney Stones - Wang T; Xia Q; Chen X; Jin X (Dove Medical Press, 2020)
Tengteng Wang, Qinghua Xia, Xiude Chen, Xunbo Jin Department of Urology, Shandong Provincial Hospital Affiliated to Shandong University, Jinan, Shandong, People’s Republic of ChinaCorrespondence: Xiude ChenDepartment of Urology, Shandong Provincial Hospital Affiliated to Shandong University, Jinan, Shandong 250014, People’s Republic of ChinaTel +86 15168863866Email scistone_2019@163.comBackground and Aim: Baidu, currently the top online search tool in China, has developed an internet search trends gathering and analysis tool called the Baidu Index. The aim of this study was to explore the value of the Baidu Index for monitoring online kidney stones-related information-seeking behavior and understanding of population features and priorities in China.Materials and Methods: The Baidu Index was queried using the term “kidney stones” for the period 2014– 2018. The search volume was recorded as well as a demand graph, with a geographic and demographic distribution. For surgical treatment modalities, the medical term “extracorporeal shock wave lithotripsy (ESWL)” was analyzed and then compared to the term “kidney stone surgery” to assess changes.Results: The search trend for the term “kidney stones” remained sustained growth over time. Searches were mostly presented by the age 20– 49, in males in the south of China. The demand graph indicated that the diagnosis, followed by the treatment, and dietary control of kidney stones had received the most attention. The search volume related to ESWL showed a similar increasing trend, but was searched with a greater volume than the term “kidney stone surgery” for most of the last 5 years.Conclusion: The Baidu Index is a useful tool to track online health information-seeking behavior of internet users in China. The geographic and demographic characteristics in kidney stones seem to be reflected in online search trend data to some extent.Keywords: search engine, Baidu Index, kidney stones, kidney stone surgery, extracorporeal shock wave lithotripsy